Effective Management of Closed Hypereutrophic Estuaries Requires Catchment-Scale Interventions - Lemley, Daniel A.; Lamberth, Stephen J.; Manuel, Warren; Nunes, Monique; Rishworth, Gavin M.; van Niekerk, Lara; Adams, Janine B. (Frontiers in Marine Science, 2021)
Increased nutrient loading associated with rapid population growth is the leading cause of deteriorating water quality in urbanized estuaries globally. Small estuaries are particularly sensitive to changes when connection with the marine environment is restricted, or lost, because of high water retention. The temporarily closed Hartenbos Estuary (South Africa) is an example of how such pressures can culminate in a severely degraded ecosystem. Wastewater treatment work (WWTW) discharges introduce substantial volumes of freshwater (8,000 m3 d–1) and nutrient loads (38 kg DIN d–1 and 22 kg DIP d–1) into this estuary. This constant inflow has necessitated frequent artificial breaching (inducing alternating states) of the estuary mouth to prevent flooding of low-lying developments and, occasionally, to mitigate against extreme events such as fish kills and sewage spills. This study investigated the efficacy of artificial mouth breaching practices in eliciting responses in selected abiotic and biotic parameters. Microalgal (phytoplankton and benthic diatoms), benthic macrofauna and fish community dynamics were assessed in response to mouth state and water quality conditions using a seasonal monitoring programme. The hypereutrophic nature of the Hartenbos Estuary was highlighted by persistent high-biomass phytoplankton accumulations (>100 μg Chl-a l–1), extreme dissolved oxygen conditions (0.4–20.5 mg O2 l–1) and the predominance of harmful algal bloom (HAB) events comprising Nannochloropsis sp. and Heterosigma akashiwo. Artificial breaching of the mouth facilitated limited tidal exchange and occurred approximately bimonthly once water levels exceeded 1.9 m above mean sea level (MSL). Current pressures and management interventions have culminated in an ecosystem void of natural fluctuations and instead characterised by low diversity and shifts between undesirable states. This is highlighted by the near year-round dominance of only a few opportunistic species/groups tolerant of adverse conditions (e.g., Nannochloropsis sp., Halamphora coffeiformis, oligochaetes, estuarine round herring Gilchristella aestuaria, and southern mullet Chelon richardsonii). Therefore, catchment-scale interventions such as the diversion of WWTW discharges and restoration of hydrodynamic variability are management priorities for improving the health and biodiversity of small, closed microtidal systems such as the Hartenbos Estuary.